2013
DOI: 10.1097/aln.0b013e31829aaff4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative High Inspired Oxygen Fraction on Surgical Site Infection, Postoperative Nausea and Vomiting, and Pulmonary Function

Abstract: Background: Intraoperative high inspired oxygen fraction (FIo 2 ) is thought to reduce the incidence of surgical site infection (SSI) and postoperative nausea and vomiting, and to promote postoperative atelectasis. Methods: The authors searched for randomized trials (till September 2012) comparing intraoperative high with normal FIo 2 in adults undergoing surgery with general anesthesia and reporting on SSI, nausea or vomiting, or pulmonary outcomes. Results: The authors included 22 trials (7,001 patients) pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 85 publications
5
101
1
8
Order By: Relevance
“…Should a high FiO 2 be used and promote a decreased probability of surgical site infection [7]. Or, in case of a documented high pulmonary vascular resistance, should a high FiO 2 be used to try and mitigate this situation [8].…”
Section: Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…Should a high FiO 2 be used and promote a decreased probability of surgical site infection [7]. Or, in case of a documented high pulmonary vascular resistance, should a high FiO 2 be used to try and mitigate this situation [8].…”
Section: Oxygenmentioning
confidence: 99%
“…Pre-oxygenation to prevent hypoxia during laryngoscopy [3] Formation of atelectasis & shunt [3] Post-oxygenation to reduce emergence hypoxia [3] Alveolar collapse & shunt [3] May decrease surgical wound infection [7] Risk of Acute Lung Injury [10] Decrease pulmonary vascular resistance [8] Higher lung inflammation in spontaneous ventilation [9] Use oxygen judiciously, if possible find other means to improve oxygenation before increasing FiO2, remember the advantages of PEEP and recruiting maneuvers [3]. …”
Section: Positive Actions Referenc E Negative Actions Referencementioning
confidence: 99%
“…Several meta-analysis have shown that the administration of high FIO 2 (0.8) compared to lower (0.3) seems to reduce surgical site infection (33). The effect might be due to an increase in partial pressure of tissue oxygen PtsO 2 because an increase in partial pressure of arterial oxygen (PaO 2 ), which in turn increases the bacterycidal capacity of neutrophils and reduces local oxydative stress as we have recently shown (34,35).…”
Section: Introductionmentioning
confidence: 99%
“…On-going clinical trials continue to seek to establish the efficacy of oxygen on mortality, surgical site infections, nausea and atelectasis with varying results [43][44][45]. Likewise on-going research is attempting to position the use of hyperoxygenation in cluster headache [46] and the use of hyperbaric oxygen for various chronic wounds [47][48].…”
Section: Other Areas Of Usementioning
confidence: 99%